Predicting COVID-19 disease outcome and post-recovery conditions using machine learning - Sajid, Abul Kasem; Kabir, Fahim; Rahman, Hasibur; Kundu, Indronil; Zaman, Sheersho (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.